2013
DOI: 10.1177/1934578x1300800917
|View full text |Cite
|
Sign up to set email alerts
|

New Flavonol Glycosides from the Leaves of Triantha Japonica and Tofieldia Nuda

Abstract: Two new flavonol glycosides were isolated from the leaves of Triantha japonica, together with eight known flavonols, kaempferol 3-O-sophoroside, kaempferol 3-O-sambubioside, kaempferol 3-O-glucosyl-(1→2)-[glucosyl-(1→6)-glucoside], quercetin 3-O-sophoroside, quercetin 3-O-sambubioside, isorhamnetin 3-O-glucoside, isorhamnetin 3-O-sophoroside and isorhamnetin 3-O-sambubioside. The new compounds were identified as kaempferol 3-O-β-xylopyranosyl-(1→2)-[β-glucopyranosyl-(1→6)-β-glucopyranoside] (1) and isorhamneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…β-1,2-Glucan mainly exists as a cyclic form in some Gram-negative bacteria, such as Agrobacterium , Rhizobium , Sinorhizobium , and Brucella . Cyclic β-1,2-glucan is known as a commensal factor in Rhizobium and as an infectious factor in Brucella abortus with respect to their hosts. , Production of this glucan in the periplasm or the extracellular space for osmotic regulation has also been reported. The chain lengths of cyclic β-1,2-glucans are usually around degrees of polymerization (DPs) of 20, while it has been reported that Rhizobium meliloti produces longer cyclic β-1,2-glucans (DPs of around 40) . Cyclic β-1,2-glucan synthases are known as membrane proteins, and their reaction mechanisms are well-characterized. Linear β-1,2-glucan (unless otherwise noted, β-1,2-glucan represents the linear form) is found in Acetobacter and Xanthomonas . , Production of β-1,2-glucan with β-1,6-glucosyl branches in Escherichia coli and Pseudomonas syringae has been reported, as well. ,, In addition, sophorosides such as kaempherol 3- O -sophoroside and stevioside are found in some plants. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…β-1,2-Glucan mainly exists as a cyclic form in some Gram-negative bacteria, such as Agrobacterium , Rhizobium , Sinorhizobium , and Brucella . Cyclic β-1,2-glucan is known as a commensal factor in Rhizobium and as an infectious factor in Brucella abortus with respect to their hosts. , Production of this glucan in the periplasm or the extracellular space for osmotic regulation has also been reported. The chain lengths of cyclic β-1,2-glucans are usually around degrees of polymerization (DPs) of 20, while it has been reported that Rhizobium meliloti produces longer cyclic β-1,2-glucans (DPs of around 40) . Cyclic β-1,2-glucan synthases are known as membrane proteins, and their reaction mechanisms are well-characterized. Linear β-1,2-glucan (unless otherwise noted, β-1,2-glucan represents the linear form) is found in Acetobacter and Xanthomonas . , Production of β-1,2-glucan with β-1,6-glucosyl branches in Escherichia coli and Pseudomonas syringae has been reported, as well. ,, In addition, sophorosides such as kaempherol 3- O -sophoroside and stevioside are found in some plants. , …”
mentioning
confidence: 99%
“…8,10,19 In addition, sophorosides such as kaempherol 3-Osophoroside and stevioside are found in some plants. 20,21 In spite of this distribution and the important physiological roles of β-1,2-glucan, a low abundance of β-1,2-glucan has limited investigation of β-1,2-glucan-degrading enzymes. We first identified a glycoside phosphorylase acting on β-1,2-glucan from Listeria innocua as a β-1,2-glucan-degrading enzyme.…”
mentioning
confidence: 99%
“…Flavonoid 1 liberated quercetin, glucose and xylose by acid hydrolysis. An UV spectral survey, according to Mabry et al [3], showed that the 3-position of quercetin is glycosylated. In the LC-MS, the molecular ion peak appeared at m/z 757 [M-H] -, showing that 2 mol glucose and 1 mol xylose are attached to quercetin.…”
mentioning
confidence: 99%